"Onsite-offshore" corporations: Investigating control mechanisms and their effects on human resource practices. Issue 1 (3rd October 2019) - Unknown
Abstract : Purpose: This paper aims to review the latest management developments across the globe and pinpoint practical implications from cutting-edge research and case studies. Design: This briefing is prepared by an independent writer who adds their own impartial comments and places the articles in context. Findings: It is thought that Multinational Corporations (MNCs) in emerging nations have a weak economy, and as such want to learn from the host country of their subsidiary companies. However, it can be seen that via global staffing, rotation and extensive expatriation, cultural norms and values of the home country can be maintained and transferred. The headquarters of the Emerging MNC can use this method of control to centralize their decision-making and standardize their foreign operations. Using people as a form of control can thus impact on human resource management (HRM) practices. Originality: The briefing saves busy executives and researchers hours of reading time by selecting only the very best, most pertinent information and presenting it in a condensed and easy-to-digest format.